Protection in Optical Mesh Networks - A Cost Effective Strategy Based on Topological Constraints - SHEELA, D.; CHELLAMUTHU, C. (Malaysian Journal of Computer Science, 2012)
The physical topology of optical networks imposes significant effects on the wavelength requirements and the associated network cost. Some work on this topic has already appeared, but the impact of topologies on survivability, which is a prime issue in optical networks, is a nascent topic. This paper proposes a protection strategy in which the topological constraints are incorporated in a survivable network design, to achieve a cost effective solution. The performance metrics are recovery percentage against link failures and total network cost. Since the topological constraints imposed involve the forbidden nodes, the recovery performance is presented for node failures as well. To study the robustness to variations in traffic demand patterns, the proposed approach is evaluated with both uniform traffic and random traffic patterns, in the existing backbone networks of distinctly different topological characteristics. The proposed method is shown to yield promising results compared to the existing methods on optical network protection.